BthTX-I from Bothrops jararacussu induces apoptosis in human breast cancer cell lines and decreases cancer stem cell subpopulation - Bezerra, Patrícia Heloise Alves (J Venom Anim Toxins Incl Trop Dis, 2019)
BACKGROUND: Breast cancer is the neoplasm with both the highest incidence and mortality rate among women worldwide. Given the known snake venom cytotoxicity towards several tumor types, we evaluated the effects of BthTX-I from Bothrops jararacussu on MCF7, SKBR3, and MDAMB231 breast cancer cell lines. METHODS: BthTX-I cytotoxicity was determined via MTT 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazoliumbromide assay. Cell death was measured by a hypotonic fluorescent solution method, annexin-V-FITC/propidium iodide staining and by apoptotic/autophagic protein expression. Cancer stem cells (CSCs) were quantified by flow cytometry using anti-CD24-FITC and anti-CD44-APC antibodies and propidium iodide. RESULTS: BthTX-I at 102 µg/mL induced cell death in all cell lines. The toxin induced apoptosis in MCF7, SKBR3, and MDAMB231 in a dose-dependent manner, as confirmed by the increasing number of hypodiploid nuclei. Expression of pro-caspase 3, pro-caspase 8 and Beclin-1 proteins were increased, while the level of the antiapoptotic protein Bcl-2 was diminished in MCF7 cells. BthTX-I changed the staining pattern of CSCs in MDAMB231 cells by increasing expression of CD24 receptors, which mediated cell death. CONCLUSIONS: BthTX-I induces apoptosis and autophagy in all breast cancer cell lines tested and also reduces CSCs subpopulation, which makes it a promising therapeutic alternative for breast cancer.